Compulsory face mask policies do not affect community mobility in Germany - Roxanne Kovacs; Maurice Dunaiski; Janne Tukiainen (ZBW – Leibniz Information Centre for Economics, 2020)
There is currently a heated debate about whether to introduce policies requiring the general public to wear protective face masks to contain COVID-19. A key concern is that compulsory face mask policies will make the public feel safer (due to risk compensation), and may consequently undermine the most important public-health advice to contain COVID-19 – which is to reduce mobility and maintain social distancing. This study provides first evidence on the impact of compulsory face mask policies on community mobility. We use a difference-in-differences design, which exploits the staggered implementation of compulsory face mask policies by German states. We use anonymised GPS data from Google's Location History feature to measure daily mobility in public spaces (groceries and pharmacies, transport hubs and workplaces). We find no evidence that compulsory face mask policies affect community mobility in public spaces in Germany. The evidence provided in this paper makes a crucial contribution to ongoing debates about how to best manage the COVID-19 pandemic.
Keywords: D9; H12; I12; I18; 330; COVID-19; face masks; social distancing; community mobility